Birds from the Sapo river basin, Morazán department, El Salvador - Herrera-Serrano, Néstor; Domínguez-Miranda, Juan Pablo (Revista Minerva, 2023)
A review was made of the bird species registered in different sites that are part of the upper watershed of the Sapo river, a continuous forest ecosystem in different states of succession of 6,000 hectares, which represent the largest private protected area that could be established in El Salvador. This standard list, generated from field visits and the review of multiple sources, including 28 ornithological works, can help to make a bird analysis and its importance, especially for the protection of vulnerable and little-known species in the country. This in order to create a mechanism to help protect this area. From this review, we recorded a total of 231 species, the first published record of the Buff-collared Nightjar (Antrostomus ridgwayi), as a new species for the country. The Mountain Trogon (Trogon mexicanus) which for El Salvador is only known in the mountains of the department of Morazán and the new national distribution of Black Swift (Cypseloides niger), Rufous-necked Wood-Rail (Aramides axillaris) and Black-throated Blue Warbler (Setophaga caerulescens).